A new performance test to evaluate the sulfate resistance of concrete by tensile strength measurements - Volkert Feldrappe; Johannes Haufe; Andreas Ehrenberg; Anya Vollpracht; Thomas Matschei (Acta Polytechnica CTU Proceedings)
Concrete structures without sufficient durability can be damaged by sulfates in groundwater and from surrounding rock layers. To evaluate the performance of a concrete mixture, precise and performance-oriented test methods are a must. Therefore, a new a performance oriented concrete test procedure based on tensile strength measurements was developed considering experiences reported in international literature and recommendations of state-of-the-art reports. A vast parameter study with approx. 3850 tensile tests on ASTM briquets, 1900 flexural tensile tests on standard prisms and 2100 expansion tests on mortar flat prisms of different ages and with different storage conditions was statistically assessed. Based on the results a performance-oriented test method could be defined which considers not only the chemical, but also the physical resistance of a concrete against sulfate attack. The method was verified by 23 concretes with different cements or cement fly ash combinations and additional field tests. It could clearly be demonstrated that the results represent the performance of a practical concrete in case of sulfate attack. Furthermore, it leads much faster to an evaluation of the sulfate resistance compared to the most other practical oriented methods.